2016
DOI: 10.1080/00036846.2016.1265074
|View full text |Cite
|
Sign up to set email alerts
|

Financial development, institutions, and poverty alleviation: an empirical analysis

Abstract: The aim of this paper is to empirically analysewhether the level of institutional quality influences the effect of financial development on poverty for a sample of developing countries covering the period from 1984 to 2012, or not. Using an interaction term constructed as a product between financial development and institutional qualitywe find that the pro-poor impact of financial development decreases as the quality of institution rises. Such differential effect can be ascribed to the capacity of banks to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 31 publications
4
21
0
Order By: Relevance
“…However, Kiendrebeogo and Minea (2016) report that financial instability increases poverty in their panel estimates for CFA Franc Zone countries, thereby counteracting the direct poverty reducing effect of financial development. Cepparulo et al (2017) use both cross-section and panel estimates for up to 58 countries over the period 1984-2012. They show that financial development (proxied by the ratios of private credit, M3 and bank assets to GDP) reduces headcount poverty but less so if institutional quality is high.…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Kiendrebeogo and Minea (2016) report that financial instability increases poverty in their panel estimates for CFA Franc Zone countries, thereby counteracting the direct poverty reducing effect of financial development. Cepparulo et al (2017) use both cross-section and panel estimates for up to 58 countries over the period 1984-2012. They show that financial development (proxied by the ratios of private credit, M3 and bank assets to GDP) reduces headcount poverty but less so if institutional quality is high.…”
Section: Previous Studiesmentioning
confidence: 99%
“…We prefer using a large panel of countries with 5-year averages. Except for Seven and Coskun (2016), Cepparulo et al (2017), and Rashid and Intartaglia (2017), previous panel studies employ annual data. We use five-year non-overlapping averages for three reasons (see also Dabla-Norris et al, 2015;de Haan & Sturm, 2017).…”
Section: Previous Studiesmentioning
confidence: 99%
“…There is a clear link between economic growth, poverty alleviation and the degree of development of the financial sector (e.g. Cepparulo et al (2017)).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Cepparulo et al (2016) analysed whether institutional quality determined how financial development influences poverty, for some developing countries over the period 1984–2012. Using an interaction term of financial development and governance quality, they found that the poverty-reduction effect of financial development adjusts with increased institutional quality.…”
Section: Literature Reviewmentioning
confidence: 99%